2011
DOI: 10.1097/psy.0b013e318234e628
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mindfulness Training on Body Awareness to Sexual Stimuli

Abstract: Objectives Treatments of female sexual dysfunction have been largely unsuccessful because they do not address the psychological factors that underlie female sexuality. Negative self-evaluative processes interfere with the ability to attend and register physiological changes (interoceptive awareness). This study explores the effect of mindfulness meditation training on interoceptive awareness and the three categories of known barriers to healthy sexual functioning: attention, self-judgment, and clinical symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
3
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(92 citation statements)
references
References 68 publications
4
80
0
3
Order By: Relevance
“…Mindfulness meditators were more aware of their visceral responses and thereby more aware of their emotions. In another study, Silverstein, Brown, Roth, and Britton (2011) reported evidence of increased interoceptive awareness in female undergraduates engaged in mindfulness training. They suggested that women who were distracted by emotionally driven self-evaluative thoughts were much slower in registering their bodily reactions, as measured by reaction time in rating physiological response to sexual stimuli, whereas mindfulness meditation training increased awareness of bodily reactions by decreasing self-evaluative thoughts.…”
Section: Full and Accurate Awarenessmentioning
confidence: 99%
“…Mindfulness meditators were more aware of their visceral responses and thereby more aware of their emotions. In another study, Silverstein, Brown, Roth, and Britton (2011) reported evidence of increased interoceptive awareness in female undergraduates engaged in mindfulness training. They suggested that women who were distracted by emotionally driven self-evaluative thoughts were much slower in registering their bodily reactions, as measured by reaction time in rating physiological response to sexual stimuli, whereas mindfulness meditation training increased awareness of bodily reactions by decreasing self-evaluative thoughts.…”
Section: Full and Accurate Awarenessmentioning
confidence: 99%
“…Compared to controls, Silverstein, Brown, Roth, and Britton [34] found improvement in awareness of physiological activation in response to sexual slides in university subjects after a 30-h mindfulness meditation program. The levels of awareness for women were similar to those of men after the intervention.…”
Section: Mindfulness and Women's Awareness Of Sexual Arousalmentioning
confidence: 96%
“…This is even more prevalent in women with a diagnosis of female sexual arousal disorder [27]. However, mindfulness interventions have proven effective in increasing concordance of physiological and perceived sexual arousal in women [14,34].…”
Section: Mindfulness and Women's Awareness Of Sexual Arousalmentioning
confidence: 97%
“…Mindfulness meditators were more aware of their visceral responses and thereby more aware of their emo tions. In another study, Silverstein et al (2011) report evidence of increased interoceptive awareness in female undergraduates engaged in mindfulness training. These authors suggest that women who were distracted by emotion ally driven self-evaluative thoughts were much slower in registering their b odily reactions, as measured by reaction time in rating physiological response to sexual stimuli, whereas mindfulness meditation training increased aware ness of bodily reactions by decreasing self-evaluative thoughts.…”
Section: Indd 177mentioning
confidence: 99%